Warrior women remaking postsecondary places through relational narrative inquiry - Young, Mary Isabelle; Joe, Lucy. (Bingley, U.K. : Emerald, 2012)
Warrior Women makes visible the ongoing intergenerational narrative reverberations (Young, 2003; 2005) shaped through Canadas residential school era which denied the communal and cultural, economic, educational, human, familial, linguistic, and spiritual rights of Aboriginal people. Attending to these narrative reverberations foregrounded the continuing colonial barriers faced by six Aboriginal post secondary students as they composed their lives in a current era of increasing standardization in Canadian universities and schools. Yet, what also became visible were ways in which the Aboriginal teachers increasingly reclaimed or drew upon their ancestral ways of knowing and being. In this retelling and reliving of their stories to live by (Connelly & Clandinin, 1999) the teachers were composing counterstories (Lindemann Nelson, 1995). While they wakefully composed and lived out these counterstories with intentions of interrupting dominant social, cultural, and institutional narratives they were, at the same time, alongside children, youth, grandchildren, family members, community members, Elders, and colleagues with whom they interacted, co-composing new possible intergenerational narrative reverberations. These new possible intergenerational narrative reverberations carry significant potential to reshape the future life possibilities of Aboriginal and non-Aboriginal children, youth, families, and communities in Canada; they also carry significant potential to reshape the school and post secondary places experienced by future generations of Aboriginal and non-Aboriginal post secondary students.
Not tomorrow ... today / Mary Isabelle Young ... [et al.] -- Introducing ourselves : storied experiences shaping the stories we live by / Mary Isabelle Young ... [et al.] -- Co-composing relational narrative inquiry / Mary Isabelle Young ... [et al.] -- Reclaiming and maintaining our Aboriginal ancestry / Mary Isabelle Young ... [et al.] -- Reclaiming our ancestral knowledge and ways : Aboriginal teachers honouring children, youth, families, elders, and communities as relational decision makers / Mary Isabelle Young ... [et al.] -- Becoming 'real' aboriginal teachers : counterstories as shaping new curriculum making possibilities / Mary Isabelle Young ... [et al.] -- Being included in and balancing the complexities of becoming an Aboriginal teacher / Mary Isabelle Young ... [et al.] -- Sharing our forward looking stories / Mary Isabelle Young ... [et al.].
Includes bibliographical references.
Keywords: Education -- Higher; Education -- General; Higher & further education, tertiary education; Educational: English literature; Indigenous peoples -- Education (Continuing education) -- Canada; Teachers -- Canada; Off-reservation boarding schools -- Canada -- History; Narrative inquiry (Research method) -- Case studies